Car Number Plate Recognition System (International Journal of Engineering and Computer Science, 2014)
The objective is to design an efficient vehicle identification system using the vehicle number plate. The system is implemented for a Housing society or a private colony. The system first loads the image of vehicle registration plate. OCR technique is used for character recognition. The original image which is stored in the application folder will be compared with the loaded image. The system will then verify whether the image is original or fake if the image is authenticated the gate will open indicated by glowing green led else gate will remain closed and a message will be sent to the security personnel.